The First Electrolytic Copper Refinery in the USA at the Chemical Copper Co. Phoenixville, Pa – History Revisited - W. W. Culver; P. J. Mackey; B. Wesstrom; E. Wraith (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
Electrodeposited copper of the 1860s was of unprecedented purity, although the profound significance of this achievement was not fully realised until the dawn of the electrical age a decade or so later. By the 1870s there were three somewhat large (4 to 4.5 tonnes Cu/day) electrolytic copper refineries in Germany based on J. B. Elkington’s process, first patented in the United Kingdom in 1865. More such refineries were planned throughout Europe. At the same time, copper output in the U.S.A. was starting to expand and with the spread of European electrolytic copper refining technology across the Atlantic, the door opened to major increases in North American output. The technology was first taken up in 1879 by James Douglas at the Chemical Copper Company in Phoenixville, Pennsylvania, where he was Superintendent. Douglas was assisted in this pioneering work by Edward Weston. The copper refinery at the Chemical Copper Company was small, not unlike the first plants in Europe. The present authors contend that the electrolytic copper refinery at the Chemical Copper should be regarded as the first copper refinery in the United States. The Balbach Copper Refinery in New Jersey, which commenced operations in 1883 with an initial production of about 2 tonnes Cu/day, has been erroneously considered as the “first commercial refinery”; it rightly belongs in second place. The early developments at these plants are discussed in this paper. INTRODUCTION In the mid-1800s, the main uses for copper were as sheathing on the wooden sailing ships of the day to protect from marine growth, boiler components in locomotives and steam engines, along with some construction uses. Copper ores were generally smelted, and further fire-refined for market. The recovery of gold and silver, if present in payable amounts, was a slow and relatively expensive step. This situation regarding copper would change by the 1870s with advances in the generation and use of electricity. The introduction of the dynamo led to major developments in electrorefining. First demonstrated in principle by Faraday in 1831 (Faraday, 1832), the dynamo was subsequently adapted and further developed by J.S. Woolrich for electro-metallurgical applications in 1842 (Woolrich, 1842; Napier, 1845). It provided a new source of power with the unprecedented potential to significantly change the scale of metal production by electrometallurgy. Interestingly enough, copper would be needed for the electrical age just beginning. By 1869, advances in dynamo design offered relatively reliable large machines, which enabled J. B. Elkington in the United Kingdom to use the dynamo in the radically new Pembrey copper electrorefinery — the first copper electrorefinery in the world (Wraith, 2013). Initial production at Pembrey was small — in the range of 1 to 2 tonnes/day — while gold and silver were recovered more readily by the treatment of the slimes than with methods used hitherto.